Type V Protein Secretion Pathway: the Autotransporter Story - Henderson, Ian R. (American Society for Microbiology, 2004)
Gram-negative bacteria possess an outer membrane layer which constrains uptake and secretion of solutes and polypeptides. To overcome this barrier, bacteria have developed several systems for protein secretion. The type V secretion pathway encompasses the autotransporter proteins, the two-partner secretion system, and the recently described type Vc or AT-2 family of proteins. Since its discovery in the late 1980s, this family of secreted proteins has expanded continuously, due largely to the advent of the genomic age, to become the largest group of secreted proteins in gram-negative bacteria. Several of these proteins play essential roles in the pathogenesis of bacterial infections and have been characterized in detail, demonstrating a diverse array of function including the ability to condense host cell actin and to modulate apoptosis. However, most of the autotransporter proteins remain to be characterized. In light of new discoveries and controversies in this research field, this review considers the autotransporter secretion process in the context of the more general field of bacterial protein translocation and exoprotein function.